Itàlia i la configuració de la llegenda negra borgiana. - ROIG MATOSES, JOAN EMILI (Scripta, 2015)
The black legend of Borgia's family began in Italy and Italians began in the fifteenth century. Created by reporters, cardinals... and contrary to what you might think, not this black legend began after the death of the second Pope Alexander VI Borja but the cardinal time, and of his pontificate, after his death and continue over the following centuries with false accusations as simony, the incest, murder.